Working conditions and occupational risk exposure in employees driving for work. (April 2016) - Fort, Emmanuel; Ndagire, Sheba; Gadegbeku, Blandine; Hours, Martine; Charbotel, Barbara
Highlights: About a quarter of employees are exposed to occupational road driving. Constraints related to working hours and work time were more frequent among employees to occupational road driving. Exposed workers exhibited more decision latitude when compared to non-exposed workers. A limited number of published studies have examined the linkage between working conditions and work-related road exposure. Abstract: Introduction: An analysis of the occupational constraints and exposures to which employees facing road risk at work are subject was performed, with comparison versus non-exposed employees. Objective was to improve knowledge of the characteristics of workers exposed to road risk in France and of the concomitant occupational constraints. The descriptive study was based on data from the 2010 SUMER survey (Medical Monitoring of Occupational Risk Exposure: Surveillance Médicale des Expositions aux Risques professionnels ), which included data not only on road risk exposure at work but also on a range of socio-occupational factors and working conditions. Materials and methods: The main variable of interest was "driving (car, truck, bus, coach, etc.) on public thoroughfares" for work (during the last week of work). This was a dichotomous "Yes/No" variable, distinguishing employees who drove for work; it also comprised 4-step weekly exposure duration: <2 h, 2–10 h, 10–20 h and ≥20 h. Results: 75% of the employees with driving exposure were male. Certain socio-occupational categories were found significantly more frequently: professional drivers (INSEE occupations and socio-occupational categories (PCS) 64), skilled workers (PCS 61), intermediate professions and teaching, health, civil service (functionaries) and assimilated (PCS 46) and company executives (PCS 36). Employees with driving exposure more often worked in small businesses or establishments. Constraints in terms of schedule and work-time were more frequent in employees with driving exposure. Constraints in terms of work rhythm were more frequent in non-exposed employees, with the exception of external demands requiring immediate response. On the Karasek's Job Demand-Control Model, employees with driving exposure less often had low decision latitude. Prevalence of job-strain was also lower, as was prevalence of "iso-strain" (combination of job-strain and social isolation). Employees with driving exposure were less often concerned by hostile behavior and, when they did report such psychological violence (inspired on the Leymann questionnaire), it was significantly more frequently due to clients, users or patients. Discussion: Employees with driving exposure at work showed several specificities. The present study, based on a representative nationwide survey of employees, confirmed the existence of differences in working conditions between employees with and without driving exposure at work. In employees with driving exposure, constraints in terms of work-time and rhythm increased with weekly exposure duration, as did tension at work and exposure to hostile behavior.